Efeito do alongamento na musculatura antagonista no teste de 10 rm e na dor muscular no exercício crucifixo reto - Chaves, Matheus Weyne (2016)
The aim of this study was to evaluate the effect of static stretching the antagonist muscles preceding the 10 MR test in dummbell flyes, and the effect of the exercise performance and perception of pain. The study included 14 subjects (24 ± 3 years of age, 75.4 ± 14,2kg, 162.3 ± 42.2 cm) with previous experience in strength training (7 experimental group and 7 in the control group), students of the Institute of Physical Education from Federal University of Ceará (IEFES-UFC) and other potential stakeholders to cooperate voluntarily with the study. Subjects performed 10 MR tests and subjective perception of pain (PSD) in the dummbell flyes and were evaluated in the pre and post the experimental group after the application of the antagonist stretching protocol, compared with the control group to test the effectiveness of the proposed methodology for application in strength training. Stretching group antagonist (ALONG) who performed the intervention was to pre- and postintervention values 14.14 ± 7.67 and 15.29 ± 7.93, and the control group (CONTR) 15.43 ± 5.50 and 16 29 ± 6.37. The differences were not presented clear results between the values of estandardardized mean difference analysis and confidence intervals for the two groups at 10 MR test. The variable PSD did not present compelling values in ALONG group, and got little difference in the CONTR group, which we believe is given by little familiarize the group with the movement. Before obtained in the study, the antagonist stretching showed no convincing effect on performance in the 10 RM test in straight crucifix when compared with the control group. We suggest that in future research more homogeneous samples are employed, more fatigue meters and more studies using the same analysis that this study.